رموز الغزل والخمرة عند حافظ الشيرازي - محمود, عيد; حسن, طلال; زليخـــة, سمر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يدور الحديث في هذا البحث على الشيرازي وشعره الغزلي, وطبيعة رموزه الغزلية. جاءت المقدّمة لتعريف الشِّيرازي, الَّذي عرفته الآداب العالميَّة، لكنّ شعره لم يترجم إلى العربيَّة إلّا حديثاً، لذلك فإنَّ من الضرورة بمكان تعريف شعره الذي كان له أثرٌ بالغٌ في الأدب العالمي كما رأى جوته. وفي التمهيد: كان الكلام على شعر الشيرازي المقروء بالعربيَّة، والمترجم وفق رؤية المترجمين, وقراءاتهم الفارسيَّة, وعن الاختلاف في التَّرجمات ومدى تأثيرها في البنية الفنِّيَّة للنَّصِّ الأدبيِّ بصورةٍ عامَّة، والمنثورة منها على وجه التَّحديد؛ فهي, وإن أدّت المعنى، يغيب الشكل الشعري الذي يحمل الوزن والإيقاع والسلاسة والطرب، وهو ما اشتهر به حافظ الشيرازي. وقد حاول البحث قراءة الرُّموز الغزليَّة المستخدمة في شعر الشيرازي، وهي رموز مستقاةٌ من الطَّبيعة كالورد والسَّرو والبلبل والببَّغاء وسواها، إضافةً إلى الخمرةِ ذات الكُنْهِ المعرفيِّ. وغالباً ما تأتي الأوصاف الغزليَّة ممزوجة بالخمرة إمَّا في مجلسها أو لونها أو طعمها فتقدّم الرموز الغزليَّة بين يدي الخمرة والخمّار. إضافة إلى ذلك يحوي البحث إشارةً إلى الرموز القرآنيَّة الَّتي جاءت لغاية الغزل, كقصَّة النبي يوسف(ع), المعروف بالجمال والموصوف به, وقُدِّمت أيضاً بعض ملكات النبي سليمان(ع) بوصفهنّ علامات دالةً على الجمال, ومن ذلك تشبيه الثغر بخاتم سليمان وغيرها, ثم تأتي النتيجة التي خلص إليها البحث. This research is about AL-Shirazi's courtship poetry and the nature of its courtship symbols. The introduction introduces AL-Shirazi, a poet who is known by the universal arts; however, his poetry, has only been recently translated into Arabic; so, it is necessary to introduce his poetry which had a great effect on the universal literature, as Guta saw. In introducing the subject, the focus was on Hafez's Arabic poetry and the translated one according to the interpretation of the translators and their readings in the Persian language. As for differences between the translations and their effect on the artistic structure of the literary text in general and the prosaic ones in particular, though they deliver meaning, but the poetic structure that carries meter, tone, fluency, and hilarity, for which Hafez AL-Shirazi was famous, will be absent. Nevertheless, this research tried to decode the courtship symbol used in Hafez's poetry which is derived from nature such as rose, cypress, bulbul, parrot, etc, in addition to wine that refers to the essence of knowledge. The courtship expressions often come mixed with wine either in its place, color, or test, so that the courtship symbols are presented by the hand of wine or waiter. This research also points the Quranic symbols that serve courtship such as the prophet Joseph (blessed) who is known for his beauty, and some merits of the prophet Solomon (blessed) that refer, in general, to beauty, such as comparing a mouth to Solomon's ring and other examples. Then comes the result the research came up with .